2016
DOI: 10.1002/glia.23029
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of transferrin and thyroid hormone during oligodendrogenesis In vitro

Abstract: Thyroid hormones (THs) and transferrin (Tf) are factors capable of favoring myelination due to their positive effects on oligodendroglial cell (OLG) differentiation. The first notion of a combined effect of apotransferrin (aTf) and TH emerged from experiments conducted in young hyperthyroid animals, which showed a seven-fold increase in the expression of Tf mRNA and precocious myelination when compared with control animals. The mechanism underlying this phenomenon in young hyperthyroid rats could consist of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Specifically, OPC quantities increase three-fold in the presence of T3 [69]. This effect requires the presence of the glycoprotein transferrin, which increases TRα1 expression [70]. Similar effects on oligodendrogenesis are observed in adult-derived NSCs.…”
Section: Effects On Oligodendrogenesismentioning
confidence: 63%
“…Specifically, OPC quantities increase three-fold in the presence of T3 [69]. This effect requires the presence of the glycoprotein transferrin, which increases TRα1 expression [70]. Similar effects on oligodendrogenesis are observed in adult-derived NSCs.…”
Section: Effects On Oligodendrogenesismentioning
confidence: 63%
“…High concentration of apo-Tf in the culture media of OPCs isolated from iron-deficient pups also promotes the maturation of these cells to control levels ( Badaracco et al., 2008 ). Interestingly, apo-Tf enhances the effect of the thyroid hormone on OPC maturation and in turn, the thyroid hormone promotes the synthesis of apo-Tf in OPCs ( Marziali et al., 2015 , 2016 ). The effects of apo-Tf on oligodendrocyte maturation and myelination were found to be mediated by several signaling pathways.…”
Section: Iron Homeostasis In Oligodendrocyte Developmentmentioning
confidence: 99%
“…Following the recapitulation hypothesis, which postulates that remyelination recapitulates developmental myelination (Franklin & Hinks, 1999), we postulate that, in being two well‐known factors which promote myelination (Ahlgren, Wallace, Bishop, Neophytou, & Raff, 1997; Barres, Lazar, & Raff, 1994; Escobar Cabrera et al, 1994; Escobar Cabrera, Zakin, Soto, & Pasquini, 1997) by acting coordinately at different stages of OLG differentiation (Marziali et al, 2015; Marziali, Correale, Garcia, & Pasquini, 2016), T3 and aTf concomitantly administered might show increased efficiency in favoring remyelination when compared with single treatments (Adamo et al, 2006; Franco et al,Franco et al, 2008). In testing this hypothesis, our current studies using the CPZ‐induced demyelination model proved that combined aTf + T3 treatment yielded higher MBP expression and more mature CC1+ OLG in the CC.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies by our group showed that, during myelination, THRα expression is independent of T3 modulation and regulated by aTf, while THRβ expression appears to respond exclusively to T3 stimulus. THRα1 emerged as the aTf‐regulated THR isoform, (Marziali et al, 2015, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation